Beneficial Immunomodulatory Effects of Fluticasone Propionate in Chlamydia pneumoniae-Infected Mice - Paróczai, Dóra (Pathogens, 2021)
The associations between inhaled corticosteroid (ICS) use and pulmonary infections remains controversial. Chlamydia pneumoniae (C. pneumoniae) accounts for asthma exacerbations; however, there are no data regarding ICS effects on C. pneumoniae infections. Thus, we investigated whether fluticasone propionate (FP) or budesonide (BUD) could affect C. pneumoniae infection in vitro and in vivo, focusing on the possible mechanisms that lead to potential anti-chlamydial outcomes. We performed direct qPCR to detect C. pneumoniae growth in infected, FP-treated, and BUD-treated A549 cells. Furthermore, FP or BUD was administered by inhalation to C. pneumoniae-infected mice. The recoverable C. pneumoniae was determined by indirect immunofluorescence. Expression levels of interferon (IFN)-γ and IFN-γ inducible chemokines were assessed by qPCR. We measured the protein concentrations of IFN-γ and of other cytokines that potentially participate in the anti-chlamydial response by ELISA. We found that FP treatment suppressed Chlamydia growth in A549 cells and in mice. Higher levels of IFN-γ gene expression were observed in FP-treated mice compared to the untreated and BUD-treated mice (p < 0.0001). IFN-γ and anti-chlamydial protein MIG/CXCL9 values were significantly higher after FP inhalation. Collectively, FP, but not BUD, suppressed C. pneumoniae growth in vitro and in vivo, which was likely due to the enhanced IFN-γ related responses.